2018
DOI: 10.5455/njppp.2018.8.0411729042018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cadmium and lead concentrations in different types of cosmetics products consumed in Iran

Abstract: Background: A safety assessment of cosmetic is necessary for evaluating the health risks associated with the use of these products. Aims and Objectives: The aim of this study is to assess the cadmium (Cd) and lead (Pb) concentrations in different types of cosmetics products consumed in Iran. Materials and Methods: This study was design to evaluate the content of Cd and (Pb) in 11 different types of cosmetics including lipstick, nail polish, eyeliner, eye pencil, eyeshadow, makeup cleaner, mascara, pancake, tat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Amount of chromium present in the hair colors of the present study was 88-771.5 ppb, which is higher than the permissible level of chromium in cosmetics forbidding the use of chromium at any amount (20). In addition, the concentrations of lead, cadmium, and chromium in Iranian hair colors were higher than that of foreign hair colors, which is in accordance with the results of a study conducted by Zafar Zadeh in 2018 (30).…”
Section: Effect Of Sample Ph Values On Absorption Rate Of Heavy Metalsupporting
confidence: 89%
“…Amount of chromium present in the hair colors of the present study was 88-771.5 ppb, which is higher than the permissible level of chromium in cosmetics forbidding the use of chromium at any amount (20). In addition, the concentrations of lead, cadmium, and chromium in Iranian hair colors were higher than that of foreign hair colors, which is in accordance with the results of a study conducted by Zafar Zadeh in 2018 (30).…”
Section: Effect Of Sample Ph Values On Absorption Rate Of Heavy Metalsupporting
confidence: 89%
“…where, z value for 95% confidence is 1.96, S is the standard deviation = 0.1, and d is the precision level = 0.05 obtained from a study in Sari, Mazandaran (Iran) (27).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Cr also fell within the EU permissible limit (1 mg/kg) [35,36]. Comparatively, high concentration (mg/kg) of Cd, 0.5 -1.1, 0.279 -0.781, 14.4 -37.3, ND -36.3 and 0.14 -14.28 were reported by Nnorom et al [37], Ayenimo et al [11], Al-Dayel et al [12], Omenka and Adeyi [3] and Zafarzadeh et al [38] as compared to the present study, while those reported by Khalid et al [39], Chauhan et al [40]; and Ekere et al [41] for Cd were lower. The Pb (0.008 -0.084 mg/kg) were similar in some cases to what Ekere et al [41] reported, while Nnorom [42], Chauhan et al [40] and Ekere et al [41] were higher than the present study.…”
Section: Concentration Of Heavy Metals In the Cosmetic Productsmentioning
confidence: 94%